Effect of High Myopia and Cataract Surgery on the Correlation Between Diabetic Retinopathy and Chronic Kidney Disease - Huiqian Kong; Siwen Zang; Yijun Hu; Yijun Hu; Yijun Hu; Zhanjie Lin; Zhanjie Lin; Baoyi Liu; Xiaomin Zeng; Yu Xiao; Zijing Du; Wu Guanrong; et al. (Frontiers in Medicine, 2022)
PurposeTo investigate the effect of high myopia and cataract surgery on the grading of diabetic retinopathy (DR) and their roles in the correlation between DR and chronic kidney disease (CKD).MethodsA total of 1,063 eyes of 1,063 diabetic patients were enrolled. We conducted binary and multiple multivariate regressions to analyze the ocular and systemic risk factors of DR. Based on the presence of myopia and history of cataract surgery, we divided the cases into four subgroups, namely those with high myopia, with the history of cataract surgery, with both conditions, and with neither, then determined the correlation between the stages of DR and CKD in each subgroup.ResultsIn the binary analysis, high myopia was identified as the protective factor for DR odds ratio (OR): 0.312 [95% confidence interval (CI): 0.195–0.500, p < 0.001], whereas cataract surgery was one of the independent risk factors for DR [OR: 2.818 (95% CI: 1.507–5.273), p = 0.001]. With increased stages of DR, high myopia played an increasingly protective role [mild non-proliferative DR (NPDR), OR = 0.461, p = 0.004; moderate NPDR OR = 0.217, p = 0.003; severe NPDR, OR = 0.221, p = 0.008; proliferative DR (PDR), OR = 0.125, p = 0.001], whereas cataract surgery became a stronger risk factor, especially in PDR (mild NPDR, OR = 1.595, p = 0.259; moderate NPDR, OR = 3.955, p = 0.005; severe NPDR, OR = 6.836, p < 0.001; PDR, OR = 9.756, p < 0.001). The correlation between the stages of DR and CKD in the group with neither high myopia nor cataract surgery history was the highest among all subgroups.ConclusionHigh myopia was a protective factor, whereas cataract surgery is a risk factor for DR, and both factors showed stronger effects throughout the (natural disease) grading of DR. The stages of DR and CKD showed a higher correlation after adjustment of the ocular confounding factors.